Reactive oxygen species enhance rAAV transduction by promoting its escape from late endosomes - Xiaoping Huang; Xiao Wang; Yanxuan Ren; Pingzhang Gao; Wentao Xu; Xiaolan Xie; Yong Diao (Virology Journal, 2023)
Abstract Background Recent seminal studies have revealed that endosomal reactive oxygen species (ROS) promote rather than inhibit viral infection. Some ROS generators, including shikonin and H2O2, have the potential to enhance recombinant adeno-associated virus (rAAV) transduction. However, the impact of ROS on rAAV intracellular trafficking remains unclear. Methods To understand the effects of ROS on the transduction of rAAV vectors, especially the rAAV subcellular distribution profiles, this study systematically explored the effect of ROS on each step of rAAV intracellular trafficking pathway using fluorescently-labeled rAAV and qPCR quantification determination. Results The results showed promoted in-vivo and in-vitro rAAV transduction by ROS exposure, regardless of vector serotype or cell type. ROS treatment directed rAAV intracellular trafficking towards a more productive pathway by upregulating the expression of cathepsins B and L, accelerating the rAAV transit in late endosomes, and increasing the rAAV nucleus entry. Conclusions These data support that ROS generative drugs, such as shikonin, have the potential to promote rAAV vector transduction by promoting rAAV’s escape from late endosomes, and enhancing its productive trafficking to the nucleus.